ANALISIS PENERAPAN ERGONOMI PADA KARYAWAN PACKING TOKO BAHAN KUE DENGAN METODE (REBA) - Zulham Ilyas; Ario Muhammad Ikhsan, Anggito Abimanyu, Paduloh (CV. Adiba Aisha Amira, 2025)
This study focuses on the ergonomics of work posture during the packing process at Toko Bahan Kue Berkah Jaya, a bakery ingredient store located in Bekasi, Indonesia. The subject of the study is a worker with a height of 173 cm who performs tasks at a packing station with a table height of 80 cm. Observations indicate that the worker adopts a bent posture with a back angle of 25°, suggesting an ergonomic mismatch between the worker’s posture and the workstation setup. This misalignment poses a potential risk of musculoskeletal disorders (MSDs).The objective of this study is to analyze the worker’s posture during the packing process and provide ergonomic recommendations for improving workstation design. The methodology involves collecting primary data through direct observation and video documentation, followed by the application of the Rapid Entire Body Assessment (REBA) method to evaluate posture risk. The REBA score is analyzed to determine the ergonomic risks associated with the current setup.The findings highlight that the current workstation height leads to poor posture, increasing the risk of MSDs. By increasing the table height to 95-100 cm and ensuring optimal material placement within arm's reach, the ergonomic risk score is significantly reduced. The proposed improvements show a notable decrease in posture risk, with REBA scores shifting from a high-risk to a controlled category. These results demonstrate the effectiveness of ergonomic intervention in promoting better work posture and reducing musculoskeletal risk factors.